Shear rheology of methyl cellulose based solutions for cell mechanical measurements at high shear rates. Issue 9 (13th February 2023) - Büyükurgancı, Beyza; Basu, Santanu Kumar; Neuner, Markus; Guck, Jochen; Wierschem, Andreas; Reichel, Felix
Abstract : Methyl cellulose solutions that are commonly used for cell mechanical measurements were characterized in three rheometers. We found shear thinning behavior but also normal stress differences indicating the viscoelasticity of the solutions. Abstract : Methyl cellulose (MC) is a widely used material in various microfluidic applications in biology. Due to its biocompatibility, it has become a popular crowding agent for microfluidic cell deformability measurements, which usually operate at high shear rates (>10 000 s −1 ). However, a full rheological characterization of methyl cellulose solutions under these conditions has not yet been reported. With this study, we provide a full shear-rheological description for solutions of up to 1% MC dissolved in phosphate-buffered saline (PBS) that are commonly used in real-time deformability cytometry (RT-DC). We characterized three different MC-PBS solutions used for cell mechanical measurements in RT-DC with three different shear rheometer setups to cover a range of shear rates from 0.1–150 000 s −1 . We report viscosities and normal stress differences in this regime. Viscosity functions can be well described using a Carreau–Yasuda model. Furthermore, we present the temperature dependency of shear viscosity and first normal stress difference of these solutions. Our results show that methyl cellulose solutions behave like power-law liquids in viscosity and exhibit first normal stress difference at shear rates between 5000–150 000 s −1 . We construct a general viscosity equation for each MC solution at a certain shear rate and temperature. Furthermore, we investigated how MC concentration influences the rheology of the solutions and found the entanglement concentration at around 0.64 w/w%. Our results help to better understand the viscoelastic behavior of MC solutions, which can now be considered when modelling stresses in microfluidic channels.